Sproget poesi eller poesiens sprog. Et essay om og med Roman Jakobson - Götzsche, Hans (Tidsskrift for Sprogforskning, 2006)
This essay contemplates the question of whether human languages have some especially poetic features and what the special features of poetry are – as conceived of by Roman Jakobson. As is well known, Jakobson says that one of the linguistic functions is the poetic function, and to him poetry emerges out of unexpected combinations of syntax, lexical semantics, phonology and prosody underpinned by the musical features of the human voice. On the background of Jakobson’s insight that some words, i.e. mama and papa, may have a ’natural origin’ in that the sounds the newborn baby will produce spontaneously are often m (also during breastfeeding) and a (when crying), I claim that the emotional bonds established in early childhood associated with these sounds may be the experiences founding the later aesthetic perception of poetry. The way I see it the musical features may arouse emotional responses effected by these ASSOCIATIVE (semiotic) characteristics in connection with the emotional and intellectual responses effected by the REFERENTIAL (semantic) characteristics of the words. Accordingly, I claim that Jakobson’s conceptual framework is an adequate way of bringing together linguistics proper and poetry.